Rising Health Expenditure Due to Non-Communicable Diseases in India: An Outlook - Barik, Debasis; Arokiasamy, Perianayagam (Frontiers in Public Health, 2016)
Abstract: With ongoing demographic transition, epidemiological transition in India has been emerged as a growing concern in India. The share of non-communicable disease in total disease burden has increased from 31 per cent in 1990 to 45 per cent in 2010. This paper seeks to explore the health scenario of India in the wake of the growing pace of non-communicable diseases like diabetes, hypertension among Indian population using data from health and morbidity survey of the National Sample Survey Organisation (2004) and notifies about the resource needed to tackle this growing health risk. Given the share of private players (70 per cent) in Indian health system, results indicate a higher private expenditure, mostly out-of-pocket expense, on account of non-communicable diseases. A timely look into the matter may tackle a more dreadful situation in near future.